3D printed mold insert infill analysis for injection molding application - Nur Syamimi, Mohd Salleh; Ahmad Rosli, Abdul Manaf; Muhammad Syahir, Ahmad (Penerbit UMP, 2024)
Injection molding (IM) normally made from steel, such as STAVAX because of its ability to withstand molding forces such as clamping, injection, and holding force. Beside of this ability, the fabrication of steel insert requires machining as such CNC machining and electro discharge machining (EDM). In contrast, a 3D printed mold insert can overcome of these constraints as it can be printed in less time and cost compared to conventional method of insert fabrication. In this research, a mold insert is fabricated using a 3D printer with a key chain shape cavity. The 3D printed insert are printed using fused deposition modelling (FDM) 3D printer with a three different infill, namely 50%, 75%, and 100% infill percentage. This could determine the performance of the 3D printed insert with the infill percentage. After several test conducted at injection molding, it is found that the infill percentage could improve the insert life span. The 100% infill contributed to longer life of the insert compared to 50% and 75% infill percentage. As the molten polymer is injected into the mold, the polymer tends to fill the void of the insert with the infill percentage of 50% and 75%. As the insert with 100% infill is used, the void is eliminated, thus the cavity can be filled with the molten polymer efficiently. From this research, the capabilities of 3D printed mold insert with different infill percentage is determined.